Enfermería desde la atención primaria en la prevención del COVID-19 en el entorno familiar - Yulissa Viviana, Mena Viera (2021)
ABSTRACT Nursing work goes beyond the hospital setting, since in primary care its work focuses on people community, health services and different sectors that can be supported. The same that uses elements of communication, dialogue, and advocacy that is helpful for health care promoting individual, familiar and community development. The process of primary and community care in the current COVID-19 pandemic, nursing plays a fundamental role in the promotion and application of preventive actions, for this, the professional applies the dialogue, creativity, resourcefulness and empathy. The general outcome of this study was aimed to describe nursing role from primary health care in coronavirus prevention in families environment. The methodology behooves to a study with a quantitative approach, the sample was made up 15 nursing professionals at Lizarzaburu Health Center, a structured interview was applied to households around the health center neighborhood. It is concluded that the sample surveyed does have the necessary knowledge regarding the virus prevention, taking into account the necessary actions to prevent it, which indicates that nursing interventions from primary health care positively influence the prevention of this disease. Keywords: COVID-19, family environment, primary care, nursing professional Reviewed by Lic. Licett Ramos I., Mgs. ENGLISH PROFESSOR C.C 0603066960